2016
DOI: 10.1002/14651858.cd011930.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating post-extraction bleeding

Abstract: We were unable to identify any reports of randomised controlled trials that evaluated the effects of different interventions for the treatment of post-extraction bleeding. In view of the lack of reliable evidence on this topic, clinicians must use their clinical experience to determine the most appropriate means of treating this condition, depending on patient-related factors. There is a need for well designed and appropriately conducted clinical trials on this topic, which conform to the CONSORT statement (ww… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
14
0
3
Order By: Relevance
“…A recent systematic review attempted to identify evidencebased interventions for treating post-extraction bleeding in patients without anticoagulants. The authors concluded that, due the lack of Breliable evidence on this topic, clinicians must use their clinical experience to determine the most appropriate means of treating this condition^ [1]. Therefore, our standard procedure for postoperative bleeding is mostly related to management recommendations for invasive dental treatment in patients using oral antithrombotic medication [3,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review attempted to identify evidencebased interventions for treating post-extraction bleeding in patients without anticoagulants. The authors concluded that, due the lack of Breliable evidence on this topic, clinicians must use their clinical experience to determine the most appropriate means of treating this condition^ [1]. Therefore, our standard procedure for postoperative bleeding is mostly related to management recommendations for invasive dental treatment in patients using oral antithrombotic medication [3,10].…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding events are one of the leading complications after tooth extraction, with an incidence of up to 25%. These range from frequent minor bleeding to rare life-threating haemorrhagic shock, even in healthy patients [1]. Previous studies have found no significant difference in bleeding incidence between patients on oral anticoagulant therapy with the vitamin K antagonist (VKA) warfarin than with patients without anticoagulant medication [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Blood loss from socket after tooth extraction is a predictable obstacle facing dentist (1) . The incidence of post-extraction bleeding varies from 0% to 26% (2) . Regarding the high vascularization of the oral cavity and disclosure of the open socket to the patient's exploring tongue and fingers, it is difficult to achieve complete hemostasis (3) .…”
Section: Introductionmentioning
confidence: 99%
“…In that study, however, post-operative bleeding was not defined, and therefore, it can be supposed that, since bleeding is a natural event after tooth extractions, Ockerman et al [1], when referring to post-operative bleeding as the outcome of their research, clearly refer to bleeding that occurs after hemostasis which has been already reached or that has not stopped after extraction, spontaneously or by means of immediately applied simple local hemostatic measures, such as compression or/and suturing or/and hemostatic agent application. In the 2016 Cochrane systematic review about interventions for treating post-extraction bleeding [7], the latter was even defined as bleeding that continues beyond 8 to 12 h after dental extraction. Since in the result section of all studies excluded from Ockerman's review, it was clearly defined that hemostasis was always reached after extraction, and, except in those of Kale et al [2] and Kumar et al [5], who stated, however, that no side effects happened, and that post-operative bleeding did not occur in all cases, the exclusion from the review of the 5 mentioned study [2][3][4][5][6] does not appear logical, especially because all those studies aimed to find any differences between different hemostatic measures in terms of bleeding times and overall hemostatic effectiveness.…”
mentioning
confidence: 99%